EXPLORING THE PSYCHOLOGICAL BENEFITS OF YOGIC ASANAS FOR NATIONAL LEVEL BASKETBALL PLAYERS - Chaudhary, Gaurav; Dev Prakash (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper aims to investigate the psychological effects of the selected yogic asanas on stress response and anxiety among national level basketball players. As competitive pressure increases and demands athletic psychological stress, the role of yogic exercises in training to boost performance is explored in the study. An experimental, posttest-only design with randomly selected and equal numbers of high- and low-skilled male basketball players from 17 to 25 years in age was used. Participants were provided a structured yogic intervention, and psychological testing was conducted before and after the intervention. The results displayed decrease of stress and anxiety combined with enhancements of self-esteem, attention and the ability to cope with stress. Interestingly, top ranking players increased their level of mental stability more than low ranking players for the tournament games. The results imply that yogic asanas can act as a comprehensive platform for mental training, offering ideas on practice to coaches and sports psychology. Therefore the future research should look at the long term effects of the problems on psychological well being and how they influence the physiological performance.